2016
DOI: 10.1186/s12889-016-2816-4
|View full text |Cite
|
Sign up to set email alerts
|

Maternal urinary manganese and risk of low birth weight: a case–control study

Abstract: BackgroundManganese (Mn) is an essential element for humans, but exposure to high levels has been associated with adverse developmental outcomes. Early epidemiological studies evaluating the effect of Mn on fetal growth are inconsistent.MethodsWe investigated the association between maternal urinary Mn during pregnancy and the risk of low birth weight (LBW). Mn concentrations in maternal urine samples collected before delivery were measured in 816 subjects (204 LBW cases and 612 matched controls) recruited bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 45 publications
(51 reference statements)
2
9
1
Order By: Relevance
“…2009). However, urinary Mn concentrations of the study population were higher than that of the subpopulation in our previous study (Xia et al. 2016), of pregnant women from an agricultural community in California (Gunier et al.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…2009). However, urinary Mn concentrations of the study population were higher than that of the subpopulation in our previous study (Xia et al. 2016), of pregnant women from an agricultural community in California (Gunier et al.…”
Section: Discussioncontrasting
confidence: 65%
“…2015). In addition, one of our previous studies suggested that exposure to higher levels of Mn, even at levels that did not exceed the upper limit of urinary reference (10μg/L) (McClatchey 2002), was associated with an increased risk of low birth weight (Xia et al. 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In a study in Hubei Province, China, maternal pre-delivery urine manganese levels demonstrated a curvilinear association with low birth weight in female infants but a linear association in male infants. 30 Additional work to confirm our findings is needed.…”
Section: Discussionmentioning
confidence: 65%
“…32 Similar findings were obtained in a case-control study conducted in Hubei Province, China, which showed both lower and higher maternal urinary manganese measured at delivery was associated with low birth weight. 30 In contrast, in a study in Taiwan, first and second, but not third trimester maternal erythrocyte manganese levels were inversely associated with infant birth weight. 33 We found that tooth manganese levels in the second and third trimester were positively associated with birth weight, even after adjustment for covariates.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation